Multi-State Study of Meeting Domestic Violence Survivors' Needs Through Non-Residential Services and Supports, 2010 - Lyon, Eleanor ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they there received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except of the removal of direct identifiers. Users should refer to the accompany readme file for a brief description of the files available with this collections and consult the investigator(s) if further information is needed.This study examined services and supports provided by domestic violence programs. It had four main goals: Learn more about what domestic violence survivors want when they come to programs for supportive services, the extent to which survivors have had their service expectations met, and survivors' assessment of immediate outcomes associated with the services they receive. Learn more about how survivors' experiences, needs and immediate outcomes vary across demographic and domestic violence program characteristics. Identify multi-level factors associated with survivors' positive service experiences. Develop recommendations for domestic violence programs across the country for how they might improve their services. Data were collected during a nine month period from 1,467 survivors (Survivor Survey Data) from 90 domestic violence programs in four states: Alabama, Illinois, Massachusetts, and Washington. The states were chosen to maximize geographical, population, rural/urban and economic diversity. Programs were also selected (Program Survey Data) for participation by major national culturally-specific institutes and organizations, to help ensure diversity of the survivor and program samples. In addition, 10 focus groups were conducted with a total of 73 domestic violence survivors, with a focus on marginalized groups.